Table of Content - -, (Journal of Educational and Psychological Sciences, 2025)
Table of Content:1. Evaluating the Performance of Secondary Schools in the Gaza Strip in Light of the Balanced Scorecard and Its Relationship to Institutional Excellence: The Mediating Role of Organizational CommitmentDr. Mohammed Ibrahim Abu Borhom, Prof. Suleiman Hussein Al-Muzain2. Ways to improve the performance of students in the Kingdom of Saudi Arabia in the results  of international tests (PISA) from the point of view of educational supervisorsMs. Afaf Othman Al-Subhi, Ms. Wafiah Othman Al-Subhi, Prof. Abdullah Ali Al-Tamam3. The reality of distributed leadership practice among middle school principals  in Makkah Al-Mukarramah from the female teachers’ point of viewMs. Ghada Mohammed Al-Lehyani ,Dr. Aishah Hamd Al-Ghaidi4. Development of Foresight Leadership Skills for Female Principals of Public Schools  in Jeddah from Their PerspectiveMs. Haneen Siraj Mitwalli ,Co-Prof. Randa Ahmed Hariri5. Education policy document in the Kingdom of Saudi Arabia in achieving sustainable development (Analytical study)Ms. Wafiah Othman Alsubhi ,Ms. Maha Saleh Saad Alyahyan ,Prof. Fatimah Abdallah Albeshr6. The Reality of Using Artificial Intelligence Applications in Educating Students with Disabilities  in the Sultanate of Oman from the Perspective of Their TeachersDr. Khalid Saif Al-Maqrashi7. Psychometric properties of the Social and Emotional Learning Scale: Social Skills Improvement System (SSIS SEL)Ms. Norah Abdulaziz Alquwaie, Prof. Mohammad Sulaiman Alwatban8. Relationship between Sensory Learning, Recalling Styles and Speaking Proficiency: A Case Study of Yemeni EFL University StudentsMr. Abdul-Rahim Ali Al-Showthabi, Prof. Mohammed Abdo Ahmed Al-Mekhlafi, Dr. Safiah Jobran Alghamri
Keywords: Journal of Educational and Psychological Sciences